Respuesta :

B. (x-2)^2/16 + (y-1)^2/25=1

Answer:

[tex]\frac{(x-2)^2}{16} +\frac{(y-1)^2}{25} =1[/tex]

Step-by-step explanation:

The equation of an ellipse outside the origin is as follows

[tex]\frac{(x-h)^2}{a^2} +\frac{(y-k)^2}{b^2} =1[/tex]

The above is for an ellipse centered on (h, k). in this case the center is in (2,1) so [tex]h = 2[/tex] and [tex]k = 1[/tex]

So far we have:

[tex]\frac{(x-2)^2}{a^2} +\frac{(y-1)^2}{b^2} =1[/tex]

Now we find a and b, Where b is the semi-major axis and the minor semi-axis.

If the center is at (2, 1) and one focus is at (2,-2) this means there are 3 units of distance between the center and the focus. This quantity will be called c.

[tex]c=3[/tex]

Now, of one vertex is at (2,-4) this means there are 5 units of distance between the center and the vertex, this is the semi major axis of the ellipse

[tex]b= 5[/tex] ⇒ [tex]b^2=5^2=25[/tex]

and to find a:

[tex]b^2=a^2+c^2[/tex]

clearing for a:

[tex]a^2=b^2-c^2[/tex]

[tex]a^2=5^2-3^2[/tex]

[tex]a^2=25-9[/tex]

[tex]a^2=16[/tex]

Substituting in the equation of the ellipse

[tex]\frac{(x-2)^2}{16} +\frac{(y-1)^2}{25} =1[/tex]

wich is the second of the options.

ACCESS MORE